A Matter of Choice: Cypriot Interactions with the Levantine Mainland During the Late 4th–3rd Millennium BC. (April 2013) - Bolger, Diane
Abstract : Despite close connections between Cyprus and the mainland Levant during the early Neolithic, the island withdrew from the Levantine interaction sphere sometime before the Khirokitian to follow its own developmental course. It is generally believed that Cyprus remained culturally isolated until the middle of the 3rd millennium BC when traditional Chalcolithic society was transformed by internal developments on the island, as well as by contact with material culture and migratory communities from mainland Anatolia. Indications of contact between Cyprus and the eastern Mediterranean, including the Levantine mainland during the late 4th and early 3rd millennium, challenge that view. Local and regional variations in the reception of foreign cultural elements present a more complex picture, suggesting that the island's relations with its neighbours were often the result of deliberate choices by Cypriot communities to engage — or refuse to engage — in external world systems.